Creative Thinking Ability of MTs Students on the Topic of Renewable Energy: A Case Study in South OKU - Kurnia, Mega; Wiyono, Ketang; Akhsan, Hamdi; Ismet (Jurnal Phi: Kurnal Pendidikan Fisika & Terapan, 2025)
This study aims to analyse the creative thinking ability of MTs students in South OKU Regency on renewable energy material. The research sample totalled 109 ninth grade students from four MTs selected by purposive sampling. The research instrument was in the form of multiple choice questions based on TTCT (Torrance Tests of Creative Thinking) indicators consisting of fluency, flexibility, originality, and elaboration. The results showed that the average score in the range of 100 students' creative thinking ability was 41.56. The average score of each indicator is: fluency (60.54), elaboration (45.77), flexibility (32.03), and originality (22.52). The highest average score is on the fluency indicator and the lowest score is on the originality indicator. This shows that students do not have difficulty in generating many ideas, but still have difficulty in generating unique and innovative ideas. The results of this study provide a factual picture of the condition of the creative thinking skills of MTs.